(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
The list of the lichenbiota of the sandstone outcrops of geological nature monument “Kam’yana Mogyla” includes 46 species lichen-forming and 9 lichenocolous fungi of 33 genera, 23 families, 3 orders and mithosporic fungi. Among them Endococcus fusiger Th. Fr. & Almq., Intralichen lichenicola (M.S. Christ. & D. Hawksw.) D. Hawksw. & M.S. Cole та Vouauxiomyces ramalinae (Nordin) D. Hawksw. were firstly reported for Ukraine, Acarospora aff. hospitans H. Magn., Haematomma ochroleucum (Neck.) J. R. Laundon, Lecanora caesiosora Poelt, Miriquidica complanata (Körber) Hertel & Rambold, Lepraria neglecta (Nyl.) Erichsen, Protoparmelia montagnei (Fr.) Poelt & Nimis – new for plain part of Ukraine, and Lichenothelia scopularia (Nyl.) D. Hawksw. – for steppe part of Ukraine. The results of arealogical, phythoclimatical and lichenocoenothic analysis are provided.